2007
DOI: 10.1007/s00262-007-0341-0
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo readout for evaluation of dendritic cell-induced autologous cytotoxic T lymphocyte responses against esophageal cancer

Abstract: Esophageal cancer is a highly malignant disease that despite surgery and adjuvant therapies has an extremely poor outcome. Dendritic cell (DC) immunotherapy as a novel promising strategy could be an alternative for treating this malignancy. EVective DC-mediated immune responses can be achieved by raising cytotoxic T lymphocyte (CTL) response against multiple antigens through loading DCs with total tumor RNA. However, the eYcacy of this strategy Wrst needs to be evaluated in a preclinical setting. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The novelty of this report is somewhat surprising in view of the interest in dendritic cell immunotherapy for cancers, including esophageal adenocarcinoma, 43 and indicates that there is a pressing need for further studies investigating the regulation of the immune response in this disease.…”
Section: Discussionmentioning
confidence: 87%
“…The novelty of this report is somewhat surprising in view of the interest in dendritic cell immunotherapy for cancers, including esophageal adenocarcinoma, 43 and indicates that there is a pressing need for further studies investigating the regulation of the immune response in this disease.…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, only Millano et al have reported DC therapy on two ESCC patients in addition to five esophageal adenocarcinomas with some technical variations compared to our study [30]. Our results show that primed T lymphocytes have obtained the capability to lyse the tumor RNA-loaded DCs.…”
Section: Discussionmentioning
confidence: 45%
“…In the present study, cytotoxicity against normal RNA-loaded DCs was minor while lytic activity of primed T cells induced by DCs loaded with tumor RNA was significantly higher than normal RNA-loaded DCs in each patient and when comparing the average of both groups by paired t -test. Millano et al have reported enhanced lytic response against some of the studied normal tissues in esophageal adenocarcinoma suggesting the possibility of adverse effects against normal tissues in esophageal cancer [30]. Therefore, a preclinical ex vivo autologous assessment may be a wise step to include the beneficiary cases and predict the possibility of the adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this read-out system, which is based on established patient specific primary cultures, we observed that immune responses are significantly more effective in killing autologous tumor cells when DCs are transfected with total tumor RNA as compared witht DCs loaded with autologous normal RNA. Importantly, no side effects were seen against normal cells, meaning that tolerance towards normal antigens was maintained [76]. The importance of the role of DCs in esophageal squamous cell carcinoma has been previously discussed by Yang et al [77].…”
Section: Results From Clinical Trials Using DC Immunotherapymentioning
confidence: 93%
“…In the field of DC immunotherapy the first combinatorial regimens are successfully applied to several solid and nonsolid human cancers [107,[111][112][113]. For EAC the first attempts after such strategies are being made [76,105,106]. From these recent developments we may conclude that in the near future the novel combinatorial treatment regimens will significantly improve EAC patient outcomes.…”
Section: Discussionmentioning
confidence: 99%